Keturunan pemburu pemungut Lanoh terakhir di Malaysia - Hamid Mohd Isa ([Glugor], Pulau Pinang : Penerbit Universiti Sains Malaysia, 2014)
On social conditions of Lanoh an indigenous tribe of Negritos tribe in Perak.
Includes bibliographical references (page 89-92) and index.
In Malay.
Keywords: Orang Asli -- Malaysia -- Social conditions; Social change -- Malaysia; Equality -- Malaysia